Implementing an Energy Calculator in a Mobile Based Application for Solar Potential Measurement - Mohana Krishnan, S; Rawat, Saurav; Surender, M; Balakrishna, R; Anandan, R (International Journal of Engineering and Technology, 2018)
Solar photovoltaic (PV) technology has matured to become a technically viable large scale source of sustainable energy. Understanding the rooftop PV potential is critical for utility planning, accommodating grid capacity, deploying financing schemes and formulating future adaptive energy policies. The NIWE (National Institute of Wind Energy) under MNRE (Ministry of New and Renewable Energy) is an esteemed institute dedicated to Indian wind and solar renewable energy generation and monitoring. The SRRA (Solar Radiation and Resource Assessment) is a division under NIWE that is responsible for solar energy monitoring throughout India. They have created the Solar Radiation Map of India using high quality, ground measured solar data. This asks the question, whether it is possible to get a quick estimate of a solar installation. Thus, the paper explains the problems in the field of solar potential measurement and the deployment of a calculator in a mobile front platform. The mobile app would quickly and effortlessly give a rough estimate on what a solar installation could save in power consumption costs.Â Â